1989
DOI: 10.1172/jci114394
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-chemotactic activity of defensins from human neutrophils.

Abstract: MethodsWe investigated the monocyte-chemotactic activity of fractionated extracts of human neutrophil granules. Monocytechemotactic activity was found predominantly in the defensincontaining fraction of the neutrophil granules. Purified preparations of each of the three human defensins (HNP-1, HNP-2, HNP-3) were then tested. HNP-1 demonstrated significant chemotactic activity for monocytes: Peak activity was seen at HNP-1 concentrations of 5 X 10' M and was 49±20%(mean±SE, n = 9) of that elicited by 10-8 M FML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
296
0
8

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(308 citation statements)
references
References 18 publications
4
296
0
8
Order By: Relevance
“…Recently, based on the classification of these four subfamilies, a systematic nomenclature system of the chemokine ligands has been formulated (2). Except for the two transmembrane-type chemokines, CX3CL1 and CXCL16, chemokines are small (8)(9)(10)(11)(12)(13)(14), mostly cationic polypeptides with two to three intramolecular disulfide bonds (1). CCL28 (also called mucosae-associated epithelial chemokine) is a recently described CC chemokine signaling via CCR10 as well as CCR3 (3,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, based on the classification of these four subfamilies, a systematic nomenclature system of the chemokine ligands has been formulated (2). Except for the two transmembrane-type chemokines, CX3CL1 and CXCL16, chemokines are small (8)(9)(10)(11)(12)(13)(14), mostly cationic polypeptides with two to three intramolecular disulfide bonds (1). CCL28 (also called mucosae-associated epithelial chemokine) is a recently described CC chemokine signaling via CCR10 as well as CCR3 (3,4).…”
mentioning
confidence: 99%
“…Accumulating evidence points out that chemokines and antimicrobial peptides have substantially overlapping functions (11). For example, several members of the mammalian antimicrobial proteins are capable of attracting leukocytes via interactions with selected seven-transmembrane G protein-coupled receptors (12)(13)(14). Most notably, Yang et al (15) have recently demonstrated that human ␤-defensins are potent agonists for CCR6, the receptor for the chemokine CCL20 (also called liver and activation-regulated chemokine or macrophage inflammatory protein-3␣), which is produced by mucosal epithelial cells and epidermal keratinocytes upon proinflammatory stimulations that selectively attracts immature dendritic cells, memory T cells, and B cells (1,16).…”
mentioning
confidence: 99%
“…Defensins have antimicrobial activities against fungi, bacteria, and viruses as well as abilities to neutralize lethal anthrax toxin (6 -12). ␣-Defensins also facilitate and amplify the innate and adaptive immune responses because they can attract human CD4 ϩ CD45RA ϩ or CD8 ϩ T cells (13,14), immature dendritic cells (14), and monocytes (15). ␣-Defensins induce the release of IFN-␥, IL-6, and IL-10 from T cells, TNF-␣, and IL-1␤ from monocytes, and IL-8 from alveolar macrophages and intestinal and lung epithelial cell-lines (16 -21).…”
mentioning
confidence: 99%
“…Besides the antibacterial activity of HNPs, other biological functions such as chemotactic activity to native resting T cells and dendritic cells, degranulation of mast cells, regulation of complement activation, and inhibition of glucocorticoid production have been implicated [45,47,[56][57][58][59].…”
Section: Defensinsmentioning
confidence: 99%